Software requirement analysis template with automation aided system - A. Jabar, Marzanah; Azizan, Asyraf; Sidi, Fatimah; Abd Ghani, Abdul Azim (IEEE, 2012)
Software engineering practices are becoming increasingly important in order to mitigate any risk of failure that could result in costly downtime, incorrect behavior, or safety failures. Requirement elicitation is the process to systematically extract and identify the requirement of the system from a combination of human stakeholder, the system's environment, feasibility studies, market analyses, business plans, analyses of competing products and domain knowledge. Communication gaps exist between customers, engineers and project managers, and requirements information loss might occur across different software development periods. This paper researches on the variety of approaches used during user requirement analysis in the software development process. A review of user requirement analysis technique from the literature is studied by listing their advantages and limitation. A tabulated summary based on the discussion are produced to form a picture of user requirement technique. Directions for future work are then proposed, based on the review.